PROFESI KEGURUAN - Syahril Chaniago (Fakultas Ekonomi Universitas Negeri Jakarta, 2015)
Abstract Before you know what is the purpose of professional teachers in advance we will try to explain what and who is the purpose of the teacher? The teacher is a figure that bears a duty and responsibility to educate and develop the potential of the learners. To become a teacher one must and must have the ability and skills, because to do a job as a teacher is basically one of the conditions is to have all these two things, in addition to other factors are also important. Someone who wants to become teachers are required to have the ability and expertise viable, because the teacher is the main character for the achievement of educational goals in harafkan all parties. Given the teacher is one of the spearheads the success of education, the role of teacher quality should be the maximum, in terms of education and quality teachers must support the profession as a teacher.